Assessing severity of postural loading in four garifrying methods - Samuel, T.; Igbeka, J.; Kolawole, O. (2009)
Posture at work is a source of musculoskeletal load. This is in addition to the external task-induced load depending on the task, which must be minimized t9 ease the work. Four working postures com- mon to gari-frying workers in the southwestern Nigeria namely, sitting beside (S8), sitting in front (SF), alternating sitting and standing (ASS) anll standing (S) were investigated to assess severity of loading in each posture. Activities of 16 fryers were videotaped and played back for assessment using Rapid Upper Limb Assessment (RULA) technique. RULA grand score recorded were S8 7.00, S 6.50, SF 6,00 and ASS 5.75. Postural angles were also measured giving S8 36, S 50, SF 79, and ASS 50'. RULA ~sult has been confirmed by postural angle measurement, indicating that ASS has the least severity due to postural loading with the least bendingltwisting and flexion of the back during gari- frying task~ ASS posture, therefore, is recommended for gari frying in southwestern Nigeria.